2006
DOI: 10.1002/jsfa.2690
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and semicarbazide‐sensitive amine oxidase inhibitory activities of alginic acid hydroxamates

Abstract: The commercial polysaccharides of alginic acid (medium (3500 cps, 2% solution) and low (250 cps, 2% solution) viscosities) were esterified with acidic methanol (1 mmol L −1 HCl) at 4 • C with gentle stirring for 5 days to obtain methyl esters of medium-viscosity alginic acid (ME-MVA) and low-viscosity alginic acid (ME-LVA). These ME-MVA and ME-LVA were reacted with alkaline hydroxylamine to obtain medium-viscosity alginic acid hydroxamates (MVA-NHOH) and LVA-NHOH. The percentages of hydroxamic acid content in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…It was reported that the DPPH scavenging activity of low-viscosity alginic acid hydroxamates (LVA-NHOH) and medium-viscosity alginic acid hydroxamates (MVA-NHOH) were greatly increased, with IC 50 values of 0.0298 and 0.0245 mg/ml, respectively (Liu, Wu, Liang, & Hou, 2007), while little or no DPPH scavenging activity of low-viscosity alginic acid or medium-viscosity alginic acid (original material) was found at the same concentrations. Improved DPPH scavenging activity of a hydroxamate derivative of pectin was also reported (Yang, Cheng, Lin, Liu, & Hou, 2004).…”
Section: Scavenging Effects On Dpph Radicalsmentioning
confidence: 99%
“…It was reported that the DPPH scavenging activity of low-viscosity alginic acid hydroxamates (LVA-NHOH) and medium-viscosity alginic acid hydroxamates (MVA-NHOH) were greatly increased, with IC 50 values of 0.0298 and 0.0245 mg/ml, respectively (Liu, Wu, Liang, & Hou, 2007), while little or no DPPH scavenging activity of low-viscosity alginic acid or medium-viscosity alginic acid (original material) was found at the same concentrations. Improved DPPH scavenging activity of a hydroxamate derivative of pectin was also reported (Yang, Cheng, Lin, Liu, & Hou, 2004).…”
Section: Scavenging Effects On Dpph Radicalsmentioning
confidence: 99%
“… 34 Few hydroxamate derivatives were reported to be antiglycation agents, and the results of this study showed that both clinical drugs containing the hydroxamate moieties of acetH and HU to be better than AG in the reduction of AGE formation. The self-prepared pectin hydroxamates 35 , 36 and alginic acid hydroxamates 37 in our previous reports exhibited SSAO inhibitory activities and DPPH radical and hydroxyl radical scavenging activities, and both pectin hydroxamates 35 , 36 and alginic acid hydroxamates belonged to macromolecular polysaccharides. The self-prepared galacturonic acid hydroxamate 38 showed DPPH radical scavenging activities with IC 50 of 82 μM, 38 which was about 2.5-fold higher than that of acetH in this study; the self-prepared galacturonic acid hydroxamate 22 showed SSAO inhibitory activities with IC 50 of 41 μM, 22 which was about 4-fold higher than that of acetH in this study.…”
Section: Resultsmentioning
confidence: 88%